1991
DOI: 10.1038/bjc.1991.422
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of Dupan-2 in pancreatic cancer patients negative for Lewis blood group phenotype

Abstract: Summary CA19-9, a serum marker for pancreatic cancer, gives false-negative results in patients who are negative for the Lewis blood group phenotype. To determine whether other markers may compensate for this drawback, serum levels of CA50, Span-l, sialyl SSEA-1 and Dupan-2 were assayed and compared with those of CA19-9 in 207 normal subjects and in 200 patients with pancreatic carcinoma whose Lewis blood group phenotypes were confirmed. In normal subjects with the Lewis negative phenotype, the serum levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 20 publications
0
43
0
1
Order By: Relevance
“…The individuals in this study that were negative for CA 19-9 elevations may represent those genotypes. Other glycans potentially could be used to complement CA 19-9, a strategy previously attempted using various related monoclonal antibodies (47). However, only limited detection of CA 19-9-negative patients was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The individuals in this study that were negative for CA 19-9 elevations may represent those genotypes. Other glycans potentially could be used to complement CA 19-9, a strategy previously attempted using various related monoclonal antibodies (47). However, only limited detection of CA 19-9-negative patients was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most promising antibody for this purpose was DUPAN2. Separate studies demonstrated that some of the CA19 -9-low patients show elevations in DUPAN-2 (20,36), but a biomarker panel based on these assays never became established. Miyamoto and coworkers found increased levels of a novel glycan, 6-sialylated, type-1 H antigen, in three out of six pancreatic tumors that were negative for CA19 -9 (37), but the researchers did not demonstrate this structure as a blood biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…DU-PAN-2 and CA19-9 expressions are also involved in ABH (O) antigens synthesis [15]. Since 5~10% of the Japanese population are considered to lack the Le enzyme, CA19-9 is less useful to them as a tumor marker due to its negative expression [6,7,11]. Generally, therefore, individuals negative for Le a and Le b due to a lack of the Le enzyme are anticipated to show an increase of serum DU-PAN-2 in those carcinomas [6,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since 5~10% of the Japanese population are considered to lack the Le enzyme, CA19-9 is less useful to them as a tumor marker due to its negative expression [6,7,11]. Generally, therefore, individuals negative for Le a and Le b due to a lack of the Le enzyme are anticipated to show an increase of serum DU-PAN-2 in those carcinomas [6,21]. Carbohydrate antigen expressions have been proven to undergo qualitative and quantitative alterations during the normal menstrual cycle and a malignant transformation of the endometrium [1-3, Correspondence to: Masanori Yasuda, MD, Department of Pathology, Tokai University School of Medicine, Bohseidai, Isehara, Kanagawa 259-1193, Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation